In fear of the most loved ones. A comprehensive review on Capgras misidentification phenomenon and case report involving attempted murder under Capgras syndrome in a relapse of a schizophrenia spectrum disorder. (August 2019) - Karakasi, Maria Valeria; Markopoulou, Maria; Alexandri, Maria; Douzenis, Athanasios; Pavlidis, Pavlos
Abstract: The present paper aims to describe a case of a schizophrenia spectrum disorder relapse leading to attempted murder, review literature, and investigate the epidemiological data and expression of violent behavior among Capgras-related incidents. 109 case reports deriving from various scientific areas dating from 1971 to 2017 were evaluated and juxtaposed with an equivalent comparison group of random psychiatry inpatients, who were examined for the same variables. Quantitative and qualitative differences were observed between samples. High level of interpersonal violence was disclosed among Capgras-related incidents, especially towards the main care-givers, with higher propensity among male patients. Homicidal behavior was also expressed in higher levels among male patients experiencing the Capgras delusion. A multidisciplinary approach is vital for the optimal management of these incidents. Further research on the pathophysiology of Capgras delusion with the utilization of functional imaging techniques is of exceptional significance for the understanding of issues of neuroscience. Highlights: Capgras delusion literature is summarized and research limitations are discussed. Prevalence of violent behavior among Capgras-related incidents is investigated. A control group of random psychiatry inpatients was utilized for the research. High levels of interpersonal violence were disclosed especially among male patients. A new case is described involving a schizoaffective disorder relapse leading to attempted murder.